High-performance FCC (fluid catalytic cracking) catalyst and preparation method thereof
By forming a silicon-rare earth-magnesium ternary composite shell on the surface of the FCC catalyst, the problem of reducing activity caused by heavy metal pollution in the prior art is solved, the hydrothermal stability and anti-pollution performance of the catalyst are improved, and catalytic cracking is significantly improved Response performance.
Patent Information
- Application Number
- CN202411815192.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-01-10
AI Technical Summary
The activity of existing FCC catalysts decreases under heavy metal pollution, resulting in an increase in coke by-product rate, a decrease in the conversion rate of raw oil, and the difficulty in distributing existing additives is limited, which limits the performance of catalytic cracking reaction.
The method of in-situ coating after the FCC catalyst is formed, and the silicon-rare earth-magnesium ternary composite shell is formed on the surface of the catalyst by copolymerization and deposition, forming a core-shell structure, and improving the catalyst's anti-vacaner, nickel and iron pollution performance. .
It significantly improves the hydrothermal stability and catalytic cracking reaction performance of FCC catalysts, enhances the resistance to heavy metal pollution, and improves the yield of light oils and heavy oil conversion capabilities.
Smart Images

Figure CN119281370A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts and crude oil processing, and in particular relates to a high-performance FCC catalyst and a preparation method thereof. Background Art
[0002] At present, fluid catalytic cracking (FCC) is still an important process for secondary processing of crude oil. The so-called FCC reaction process refers to the crude oil processing process in which the crude oil undergoes cracking / cracking reaction under the action of FCC catalyst to produce high-value light oil products (such as gasoline, diesel, etc.) and low-carbon olefins (such as propylene). At present, the FCC process mainly adopts the riser process, and the FCC catalyst used is a microsphere solid acid catalyst with good fluidization performance, which mainly includes three main components: zeolite molecular sieve, binder and matrix. The crude oil contains heavy metal elements such as nickel, vanadium, and iron. Under the regeneration environment, the Al atoms in the zeolite molecular sieve framework will be detached from the molecular sieve framework under the action of vanadium pollutants, the specific surface area will decrease, and the active centers will decrease. When these heavy metals are deposited on the catalyst surface in large quantities, the yield of by-products such as coke will increase significantly, and the crude oil conversion rate will decrease significantly.
[0003] In view of the above problems, the existing patent CN115555011A discloses an additive for improving the heavy metal pollution resistance of FCC catalysts. The patent introduces a secondary structural unit of a magnesium-rare earth-aluminum ternary dihydroxy compound with a large specific surface, a large pore volume and excellent heavy metal pollution element passivation performance into a clay carrier structure through an acid extraction combined with a coprecipitation in-situ construction method, and then spray-dries and forms with a bonding component to obtain an additive for improving the heavy metal pollution resistance of FCC catalysts. However, this method will cause the unit with excellent heavy metal pollution element passivation performance to be evenly distributed at various positions inside the FCC catalyst, making it difficult to fully contact and react with the heavy metal pollution elements on the outer layer of the FCC catalyst, greatly limiting the catalytic cracking reaction performance of the FCC catalyst. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a high-performance FCC catalyst and a preparation method thereof.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a high-performance FCC catalyst, comprising the following steps:
[0007] (1) zeolite molecular sieve, binder, matrix material and water are mixed and slurried, and then the obtained slurry is spray-dried and calcined to obtain an FCC catalyst;
[0008] (2) The FCC catalyst obtained in step (1) is mixed with a silicon source and water, and the pH value is adjusted with aqueous ammonia. A rare earth salt and a magnesium salt are then added for copolymerization and precipitation. The high-performance FCC catalyst is obtained after standing.
[0009] Preferably, in step (1), the FCC catalyst comprises 15-70 wt% of zeolite molecular sieve, 3-20 wt% of binder and 15-60 wt% of matrix material.
[0010] Preferably, in step (1), the binder comprises one or more of silica sol, aluminum sol, silica-alumina gel, silica-alumina composite sol, aluminum phosphate sol, aluminum phosphate gel, and acidified pseudo-boehmite; and / or,
[0011] The matrix material includes one or more of kaolin, halloysite, montmorillonite, diatomaceous earth, saponite, rectorite, sepiolite, attapulgite, hydrotalcite and bentonite.
[0012] Preferably, in step (2), the silicon source includes one or more of water glass, silica sol, methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate, and butyl orthosilicate.
[0013] Preferably, in step (2), the rare earth salt includes one or more of yttrium chloride, yttrium nitrate, lanthanum chloride, lanthanum nitrate, cerium chloride, and cerium nitrate.
[0014] Preferably, in step (2), the magnesium salt includes one or more of magnesium chloride, magnesium nitrate, magnesium sulfate, and hydroxymagnesium chloride.
[0015] Preferably, in step (2), the mass ratio of the FCC catalyst, the silicon source calculated as SiO2, the rare earth salt calculated as Re2O3 and the magnesium salt calculated as MgO is 1: (0.01-0.05): (0.005-0.015): (0.001-0.01).
[0016] Preferably, in step (2), the copolymerization deposition temperature is 50-95° C. and the time is 0.5-2 h.
[0017] The present invention also provides a high-performance FCC catalyst prepared by the preparation method described in the above technical solution.
[0018] Preferably, the high-performance FCC catalyst has a core-shell structure with the FCC catalyst as the core and the silicon-rare earth-magnesium complex as the shell.
[0019] Compared with the prior art, the present invention has the following advantages and technical effects:
[0020] The present invention uses an in-situ coating method after FCC is formed to copolymerize and deposit silicon, rare earth and magnesium on the surface of the FCC catalyst and form a silicon-rare earth-magnesium ternary complex shell layer, thereby obtaining a high-performance FCC catalyst with a core-shell structure. The silicon-rare earth-magnesium ternary complex in the shell layer can be decomposed to form SiO2-Re2O3-MgO composite oxides during the high-temperature regeneration process of the FCC catalyst, wherein the inert SiO2 can improve the hydrothermal stability of the FCC catalyst, and Re2O3 and MgO can respectively improve the vanadium pollution resistance and nickel and iron pollution resistance of the FCC catalyst, thereby greatly improving the comprehensive catalytic cracking reaction performance of the FCC catalyst.
[0021] The preparation method of the high-performance FCC catalyst provided by the invention has simple process, low cost and good application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0023] Figure 1 This is the SEM image of the high performance FCC catalyst C3 prepared in Example 3. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0026] The embodiment of the present invention provides a method for preparing a high-performance FCC catalyst, comprising the following steps:
[0027] (1) zeolite molecular sieve, binder, matrix material and water are mixed and slurried, and then the obtained slurry is spray-dried and calcined to obtain an FCC catalyst;
[0028] (2) The FCC catalyst obtained in step (1) is mixed with a silicon source and water, and the pH value is adjusted with aqueous ammonia. A rare earth salt and a magnesium salt are then added for copolymerization and precipitation. The high-performance FCC catalyst is obtained after standing.
[0029] In a preferred embodiment, in step (1), the zeolite molecular sieve includes one or more of HY, HUSY, REUSY, REHY, and REY zeolite molecular sieves, preferably one or more of HUSY, REUSY, and REY zeolite molecular sieves.
[0030] In a preferred embodiment, in step (1), the binder includes one or more of silica sol, aluminum sol, silica-alumina gel, silica-alumina composite sol, aluminum phosphate sol, aluminum phosphate gel, and acidified pseudo-boehmite, preferably one or more of aluminum sol, silica-alumina composite sol, and aluminum phosphate gel. The reason why these binders are selected in the embodiment of the present invention is that the above binders can play a role in bonding the components in the FCC catalyst.
[0031] In a preferred embodiment, in step (1), the matrix material comprises one or more of kaolin, halloysite, montmorillonite, diatomite, saponite, rectorite, sepiolite, attapulgite, hydrotalcite, and bentonite, preferably one or more of kaolin, montmorillonite, diatomite, sepiolite, and bentonite. The reason why this type of matrix material is selected in the embodiment of the present invention is that the above matrix components can all play a role in assisting the formation of the FCC catalyst.
[0032] In a preferred embodiment, in step (1), the solid content of the slurry is 10-50 wt %.
[0033] In a preferred embodiment, in step (1), the calcination temperature is 450° C. and the calcination time is 0.5 h.
[0034] In a preferred embodiment, in step (1), the FCC catalyst comprises 15-70 wt% of zeolite molecular sieve, 3-20 wt% of binder and 15-60 wt% of matrix material.
[0035] In a preferred embodiment, in step (2), the silicon source includes one or more of water glass, silica sol, methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate, and butyl orthosilicate, preferably one or more of water glass, ethyl orthosilicate, and propyl orthosilicate. The reason why this type of silicon source is selected in the embodiment of the present invention is that this type of silicon source can be efficiently hydrolyzed to generate silicon-oxygen species at a certain pH value.
[0036] The silicon source in the present invention is hydrolyzed under the catalytic action of ammonia water to generate silicon-oxygen species, which are then copolymerized with rare earth salts and magnesium salts to form a silicon-rare earth-magnesium ternary complex shell on the surface of the FCC catalyst.
[0037] In a preferred embodiment, in step (2), the pH value is adjusted to 8-10; the concentration of the ammonia water is 28 wt %. The ammonia water in the present invention is used to catalyze the hydrolysis of the silicon source.
[0038] In a preferred embodiment, in step (2), the rare earth salt comprises one or more of yttrium chloride, yttrium nitrate, lanthanum chloride, lanthanum nitrate, cerium chloride, and cerium nitrate, preferably one or more of yttrium nitrate, lanthanum nitrate, and cerium nitrate. The reason why this type of rare earth salt is selected in the embodiment of the present invention is that this type of rare earth salt can be fully ionized in aqueous solution to produce rare earth ions.
[0039] In a preferred embodiment, in step (2), the magnesium salt includes one or more of magnesium chloride, magnesium nitrate, magnesium sulfate, and magnesium hydroxychloride, preferably one or two of magnesium chloride and magnesium nitrate. The reason why this type of magnesium salt is selected in the embodiment of the present invention is that this type of magnesium salt can be fully ionized in an aqueous solution to generate magnesium ions.
[0040] In a preferred embodiment, in step (2), the mass ratio of the FCC catalyst, the silicon source calculated as SiO2, the rare earth salt calculated as Re2O3 and the magnesium salt calculated as MgO is 1: (0.01-0.05): (0.005-0.015): (0.001-0.01).
[0041] In a preferred embodiment, in step (2), the copolymerization deposition temperature is 50-95° C., preferably 60-90° C.; the copolymerization deposition time is 0.5-2 h; and the copolymerization deposition is carried out in a water bath.
[0042] In a preferred embodiment, in step (2), the standing time is 1 to 4 hours.
[0043] The embodiment of the present invention also provides a high-performance FCC catalyst prepared by the preparation method described in the above technical solution.
[0044] In a preferred embodiment, the high performance FCC catalyst has a core-shell structure with the FCC catalyst as the core and the silicon-rare earth-magnesium complex as the shell.
[0045] The high-performance FCC catalyst provided by the embodiment of the present invention has excellent hydrothermal stability, resistance to vanadium pollution, and resistance to nickel and iron pollution.
[0046] In the following examples, REY zeolite molecular sieve, kaolin, and alumina sol (Al2O3 content: 18%) were purchased from the Catalyst Plant of Lanzhou Petrochemical Company of PetroChina Co., Ltd. and were qualified industrial products; tetraethyl orthosilicate, La(NO3)3·6H2O, MgCl2·6H2O, and ammonia water (concentration of 28wt%) were all commercially available analytical grade reagents.
[0047] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.
[0048] Example 1
[0049] A method for preparing a high performance FCC catalyst:
[0050] (1) 35 g of REY zeolite molecular sieve (dry basis), 55.55 g of aluminum sol, 55 g of kaolin (dry basis) and 177 g of deionized water were mixed and slurried, and the resulting slurry was spray-dried and calcined at 450° C. for 0.5 h to obtain an FCC catalyst; wherein the solid content of the slurry was 45.12 wt %, and the FCC catalyst contained 35 wt % of zeolite molecular sieve, 10 wt % of aluminum sol (based on the mass of Al2O3 contained) and 55 wt % of kaolin.
[0051] (2) 50 g of the FCC catalyst obtained in step (1), 1.74 g of tetraethyl orthosilicate and 200 g of deionized water were mixed and the pH value was adjusted to 8 with aqueous ammonia. Then, 0.66 g of La(NO3)3·6H2O and 0.25 g of MgCl2·6H2O were added (the mass ratio of FCC catalyst, tetraethyl orthosilicate calculated as SiO2, La(NO3)3·6H2O calculated as La2O3 and MgCl2·6H2O calculated as MgO was 1:0.01:0.005:0.001). The mixture was co-precipitated in a water bath at 60°C for 2 h, and then aged for 4 h. After filtering, washing and drying, a high-performance FCC catalyst C1 was obtained.
[0052] Example 2
[0053] A method for preparing a high performance FCC catalyst:
[0054] (1) 52.5 g of REY zeolite molecular sieve (dry basis), 83.33 g of aluminum sol, 82.5 g of kaolin (dry basis) and 267 g of deionized water were mixed and slurried, and the resulting slurry was spray-dried and calcined at 450° C. for 0.5 h to obtain an FCC catalyst; wherein the solid content of the slurry was 44.99 wt %, and the FCC catalyst contained 35 wt % of zeolite molecular sieve, 10 wt % of aluminum sol (based on the mass of Al2O3 contained) and 55 wt % of kaolin.
[0055] (2) 100 g of the FCC catalyst obtained in step (1), 10.42 g of tetraethyl orthosilicate and 700 g of deionized water were mixed and the pH value was adjusted to 9 with aqueous ammonia. Then, 2.66 g of La(NO3)3·6H2O and 2.53 g of MgCl2·6H2O were added (the mass ratio of FCC catalyst, tetraethyl orthosilicate calculated as SiO2, La(NO3)3·6H2O calculated as La2O3 and MgCl2·6H2O calculated as MgO was 1:0.03:0.01:0.005). The mixture was co-precipitated in a water bath at 75°C for 1 h, and then aged for 2 h. After filtering, washing and drying, a high-performance FCC catalyst C2 was obtained.
[0056] Example 3
[0057] A method for preparing a high performance FCC catalyst:
[0058] (1) 70 g of REY zeolite molecular sieve (dry basis), 111.11 g of aluminum sol, 110 g of kaolin (dry basis) and 356 g of deionized water were mixed and slurried, and then the obtained slurry was spray-dried and calcined at 450°C for 0.5 h to obtain an FCC catalyst; wherein the solid content of the slurry was 44.99 wt% and the FCC catalyst contained 35 wt% of zeolite molecular sieve, 10 wt% of aluminum sol (based on the mass of Al2O3 contained) and 55 wt% of kaolin.
[0059] (2) 150 g of the FCC catalyst obtained in step (1), 26.04 g of tetraethyl orthosilicate and 1500 g of deionized water were mixed and the pH value was adjusted to 10 with aqueous ammonia. Then, 5.98 g of La(NO3)3·6H2O and 7.57 g of MgCl2·6H2O were added (the mass ratio of FCC catalyst, tetraethyl orthosilicate calculated as SiO2, La(NO3)3·6H2O calculated as La2O3 and MgCl2·6H2O calculated as MgO was 1:0.05:0.015:0.01). The mixture was co-precipitated in a water bath at 90°C for 0.5 h, and then aged for 1 h. After filtering, washing and drying, a high-performance FCC catalyst C3 was obtained.
[0060] Figure 1 This is a SEM image of the high performance FCC catalyst C3 prepared in Example 3. Figure 1 It can be seen that the high performance FCC catalyst C3 prepared in Example 3 is spherical.
[0061] Comparative Example 1
[0062] Preparation method of conventional oil refining catalyst:
[0063] 87.5 g REY zeolite molecular sieve (dry basis), 138.88 g aluminum sol, 137.5 g kaolin (dry basis) and 442.5 g deionized water were mixed and slurried, and then the obtained slurry was spray-dried, calcined and cured at 450° C. for 0.5 h, washed with water, and dried to obtain a conventional oil refining catalyst DC.
[0064] Comparative Example 2
[0065] Step (1) is the same as in Example 1;
[0066] (2) 50 g of the FCC catalyst obtained in step (1) and 200 g of deionized water were mixed and the pH value was adjusted to 8 with aqueous ammonia. Then, 0.66 g of La(NO3)3·6H2O and 0.25 g of MgCl2·6H2O were added. The mixture was copolymerized and deposited in a water bath at 60°C for 2 h. The mixture was then aged for 4 h. After filtration, washing and drying, FCC catalyst D1 was obtained.
[0067] Comparative Example 3
[0068] Step (1) is the same as in Example 1;
[0069] (2) 50 g of the FCC catalyst obtained in step (1), 1.74 g of tetraethyl orthosilicate and 200 g of deionized water were mixed, and then 0.66 g of La(NO3)3·6H2O and 0.25 g of MgCl2·6H2O were added. The mixture was copolymerized and deposited in a water bath at 60°C for 2 h, and then aged for 4 h. After filtering, washing and drying, FCC catalyst D2 was obtained.
[0070] Comparative Example 4
[0071] Step (1) is the same as in Example 1;
[0072] (2) 50 g of the FCC catalyst obtained in step (1), 1.74 g of tetraethyl orthosilicate and 200 g of deionized water were mixed, the pH value was adjusted to 8 with aqueous ammonia, and then 0.25 g of MgCl2·6H2O was added. The mixture was copolymerized and deposited in a water bath at 60°C for 2 h, and then aged for 4 h. After filtering, washing and drying, FCC catalyst D3 was obtained.
[0073] Evaluation method:
[0074] After aging at 800℃ and 100% steam for 17h, the heavy oil catalytic cracking reaction performance of the catalyst was evaluated on the ACE device (Advanced cracking evaluation, Kayser R+MultiMode microreactor). The reaction temperature was 530℃, the catalyst-to-oil ratio was 5, the properties of the feed oil were shown in Table 1, and the heavy oil catalytic cracking reaction performance of different FCC catalysts was shown in Table 2.
[0075] Table 1 Raw oil properties
[0076] Table 2 Heavy oil catalytic cracking reaction performance of different FCC catalysts
[0077] It can be seen from Table 2 that, under the condition of the same molecular sieve content, the reaction performance of the FCC catalyst prepared by the present invention is significantly better than that of the conventional refining catalyst and the comparative catalyst, showing a stronger heavy oil conversion ability and a more excellent light oil (gasoline) yield.
[0078] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a high-performance FCC catalyst, characterized in that: The following steps are involved: (1) zeolite molecular sieve, binder, matrix material and water are mixed and slurried, and then the obtained slurry is spray-dried and calcined to obtain an FCC catalyst; (2) The FCC catalyst obtained in step (1) is mixed with a silicon source and water, and the pH value is adjusted with aqueous ammonia. A rare earth salt and a magnesium salt are then added for copolymerization and precipitation. The high-performance FCC catalyst is obtained after standing.
2. The method for preparing a high performance FCC catalyst according to claim 1, characterized in that: In step (1), the FCC catalyst comprises 15-70 wt% of zeolite molecular sieve, 3-20 wt% of binder and 15-60 wt% of matrix material.
3. The method for preparing a high performance FCC catalyst according to claim 1 or 2, characterized in that: In step (1), the binder includes one or more of silica sol, aluminum sol, silica-alumina gel, silica-alumina composite sol, aluminum phosphate sol, aluminum phosphate gel, and acidified pseudo-boehmite; and / or, The matrix material includes one or more of kaolin, halloysite, montmorillonite, diatomaceous earth, saponite, rectorite, sepiolite, attapulgite, hydrotalcite and bentonite.
4. The method for preparing a high performance FCC catalyst according to claim 1, characterized in that: In step (2), the silicon source includes one or more of water glass, silica sol, methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate, and butyl orthosilicate.
5. The method for preparing a high performance FCC catalyst according to claim 1, characterized in that: In step (2), the rare earth salt includes one or more of yttrium chloride, yttrium nitrate, lanthanum chloride, lanthanum nitrate, cerium chloride, and cerium nitrate.
6. The method for preparing a high performance FCC catalyst according to claim 1, characterized in that: In step (2), the magnesium salt includes one or more of magnesium chloride, magnesium nitrate, magnesium sulfate, and hydroxymagnesium chloride.
7. The method for preparing a high performance FCC catalyst according to claim 1, characterized in that: In step (2), the mass ratio of the FCC catalyst, the silicon source calculated as SiO2, the rare earth salt calculated as Re2O3 and the magnesium salt calculated as MgO is 1: (0.01-0.05): (0.005-0.015): (0.001-0.01).
8. The method for preparing a high performance FCC catalyst according to claim 1, characterized in that: In step (2), the copolymerization deposition temperature is 50-95° C. and the time is 0.5-2 h.
9. The high performance FCC catalyst prepared by the preparation method according to any one of claims 1 to 8.
10. The high performance FCC catalyst according to claim 9, characterized in that The high-performance FCC catalyst has a core-shell structure with the FCC catalyst as the core and the silicon-rare earth-magnesium complex as the shell.
Citation Information
Patent Citations
Hydrogenation catalyst, and preparation method and application thereof
CN107970938A
High-activity, water-resistant and thermal-stability catalyst and preparation method thereof
CN113477247A
Catalytic cracking catalyst as well as preparation method and application thereof
CN113492013A
Method for preparing catalytic cracking catalyst by ammonium-free method
CN116212849A
Efficient heavy metal pollution-resistant FCC (fluid catalytic cracking) catalyst with shell structure and preparation method of efficient heavy metal pollution-resistant FCC catalyst
CN118341474A